Performance-Based Measurement of Digital Storytelling Effects on Primary EFL Speaking: A Quasi-Experimental Study - Muhamad Zulpiani Hamdi (CENDEKIA : Jurnal Pendidikan Terintegrasi, 2026)
English-speaking proficiency is a foundational component of communicative competence in elementary EFL education; however, empirical investigations of digital storytelling at the primary level have predominantly emphasized motivational outcomes rather than rigorously measured speaking performance. This imbalance has left a methodological and conceptual gap concerning how multimodal narrative pedagogy contributes to objectively assessed oral proficiency. This study aimed to analyze the effect of digital storytelling on primary school students' EFL speaking competence across multiple performance dimensions. A quasi-experimental non-equivalent control group design was implemented in an urban public primary school involving 64 Grade 5 students assigned to experimental and control groups. Data were collected through pre- and post-performance-based speaking tests evaluated using a validated analytic rubric covering fluency, grammatical accuracy, pronunciation, vocabulary, and coherence. Inferential statistical analyses, including ANCOVA and effect size estimation, were conducted to examine group differences. The findings indicated significantly greater multidimensional gains in speaking in the experimental group, with the most substantial improvements observed in fluency and vocabulary development. These results demonstrate that digital storytelling yields measurable linguistic enhancement beyond affective engagement. The study contributes theoretically by integrating Communicative Language Teaching and Multimedia Learning Theory within an empirically validated framework, and it offers practical implications for curriculum design, formative assessment, and technology-mediated speaking instruction in elementary EFL contexts.